Ten Steps Toward the Horizon (Journal of Parents and Teachers, 2024)
The article is based on an interview with Eduardo Galeano, where a series of ideas are presented, such as the notion that to learn, one must embrace mystery or that it doesn't matter to feel lonely as long as one is feeling something. Eduardo Galeano denounced consumer society, exploitation, and marginalization, and he expressed a deep love for Latin America with humor and a sense of duty.
Keywords: denunciation; imagination